Using parametric theories to understand carrier-envelope phase and multi-color processes - Ursrey, Dustin (Kansas State University, 2024)
The interaction between intense laser pulses and matter can drive a wide range of processes: for example, atoms or molecules can undergo breakup to create new systems, excitation can occur to create products with different properties and reactivities, and chemical reactions can be affected in ways that enhance/dehance the probability of specific outcomes. Changing the incident light can alter all of these aforementioned processes, giving rise to the possibility of coherent control in an experimental setting. In order to understand the control provided over a specific observable, it is necessary to develop a theory that allows us to understand the physical mechanisms that contribute to this control, as well as how these mechanisms depend on the parameters of the incident light. This thesis will focus on our group’s parametric formalism for carrier-envelope phase (CEP) and multi-color control. Our formalism, outlined in Chap. 2, allows any observable to be expressed in terms of the interference between different photon pathways, and explicitly shows how changing the CEP or the relative phase between different colors controls this interference. Application of our formalism to understand control over dissociation is demonstrated in Chap. 3 and Chap. 6. Here, knowledge of system allows us to predict the most likely pathways taken during breakup, and the construction of observables in terms of these pathways allows for quantitative, a priori predictions about control. In Chap. 4 and Chap. 5, it will be shown that our formalism can also allow for the extraction of important physical information from a known result. Chapter 4 will focus specifically on the problem of characterizing the CEP of a pulse, showing that our formalism provides not only a deeper understanding of currently used experimental techniques, but can also offer a slight improvement in the precision of the extracted phase. Chapter 5 will focus on directly extracting photon pathways from a measured spectrum, allowing us to identify the exact physical mechanisms that must have been present to create a given feature in a measured spectrum.
Keywords: Atomic, molecular, and optical physics; Carrier-envelope phase; Coherent control; Above threshold dissociation; Computational physics